FACTORS INFLUENCING AIR CARGO POLICY DECISIONS AND IMPLEMENTATION IN NIGERIA: A STAKEHOLDER’S PERSPECTIVE - Adedotun Joseph ADENIGBO; Joash MAGETO; Rose LUKE (Transport Problems)
Policies are supposedly made such that their implementation for present growth does not hamper future development. However, it has been challenging to effectively implement some policy decisions based on stakeholders’ reactions to their sustainability in the air cargo industry. This paper examined the factors affecting air cargo policy decisions and their implementation in Nigeria by employing the quantitative research method and conducting a survey of stakeholders by random sampling at the Lagos International Airport through a well-designed research questionnaire. The data collected were analyzed using exploratory factor analysis (EFA) and partial least square structural equation modeling (PLS-SEM). Before estimating the PLS-SEM model, latent factors were constructed using EFA. The results reveal that the factors affecting the air cargo policy decisions and implementation include the policy formulation process, stakeholders’ interests and commitment, policy goals and implementation, and corruption and governance. The results imply that fundamental public policy issues prevail in Nigeria’s air cargo sector development programs. This study provides insight into the reasons behind opposition to implementing certain air cargo policy decisions in Nigeria. It offers directions for addressing the problems of poor policy decisions that do not guarantee future development. In practice, the study advocates the all-inclusive stakeholders’ involvement in Nigeria’s policy formulation process for the air cargo industry.